TA’AWUN PATTERN OF GOVERNANCE OF HAJJ FUNDS IN THE MINISTRY OF RELIGION OF THE REPUBLIC OF INDONESIA - Nasution, Nursanita; Unti, Ludigdo; Gugus, Irianto; Zaki, Baridwan (The International Journal of Accounting and Business Society, 2019)
The purpose of this study is to understand how the practice of Hajj fund management in the Ministry of Religion of the Republic of Indonesia (Kemenag RI), especially in the Sub directorate of Hajj Implementation Services (BPIH). The hajj fund was questioned by the community because of the lack of clarity in its management and indications of fraud and it was proven by the arrest of the Minister of Religion as the mandate holder of the Hajj fund in the Indonesian Ministry of Religion in 2006 for violating Law No.31 of 1999. Reform of governance of Hajj funds has not shown significant results.            This study uses an interpretive method, specifically an ethnometodology approach to reveal the daily ways in which actors in subdir BPIH in the Indonesian Ministry of Religion run or initiate their culture (Garfinkel, 1967). The data used are the results of interviews and observations.             This study found a pattern of ta'awun in the governance of the utilization of Hajj funds. The utilization of the Hajj fund is permitted by the MUI fatwa, but the pilgrims do not get a return because it is not difficult to reach the large and wide number of pilgrims in Indonesia. But the advancement of information technology with the existence of virtual accounts helps the Ministry of Religion in promoting transparency. The funds used to finance the organization of the Hajj (BPIH) are from direct costs and indirect costs. The use of this term only applies to the Ministry of Religion which is different from the understanding of accounting. Direct cost is funds deposited by pilgrims while indirect costs are funds from the optimization of deposit funds and efficient hajj. In practice the money paid by pilgrims at the beginning of registration is only to get a seat, in the year of their departure the direct cost of the amount of the BPIH for the year of departure determined by the Ministry of Religion and the House of Representatives must be paid off. In the operational implementation of the pilgrimage the lack of funds using indirect cost funds is the result of optimizing the hajj funds collected by the Ministry of Religion both from the deposit of unregistered pilgrims and the results of the efficiency of the previous year's hajj funds. Actors in subdir BPIH as Hajj fund managers agreed to understand that the use of indirect funds is indeed very much needed and is a subsidy to the form of ta'awun or help each other to help fellow prospective pilgrims.